2017
DOI: 10.1523/jneurosci.1795-17.2017
|View full text |Cite
|
Sign up to set email alerts
|

Presynaptic Neuronal Nicotinic Receptors Differentially Shape Select Inputs to Auditory Thalamus and Are Negatively Impacted by Aging

Abstract: Acetylcholine (ACh) is a potent neuromodulator capable of modifying patterns of acoustic information flow. In auditory cortex, cholinergic systems have been shown to increase salience/gain while suppressing extraneous information. However, the mechanism by which cholinergic circuits shape signal processing in the auditory thalamus (medial geniculate body, MGB) is poorly understood. The present study, in male Fischer Brown Norway rats, seeks to determine the location and function of presynaptic neuronal nicotin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
24
2
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(30 citation statements)
references
References 87 publications
3
24
2
1
Order By: Relevance
“…GABAergic subtypes with or without PNs could be expected to show different degrees of plasticity, perhaps related to signal salience or top-down modulation of the auditory brainstem, or effects of neuromodulatory inputs ( Schofield and Hurley, 2018 ). Sottile et al (2017a , b ) demonstrated nicotinic receptors associated with GABAergic tectothalamic projections, and showed further that these receptors can change during aging. The authors commented on nicotinic receptor subunits expressed in the large GABAergic IC cells, but also showed evidence for such expression in smaller GABAergic cells.…”
Section: Discussionmentioning
confidence: 88%
“…GABAergic subtypes with or without PNs could be expected to show different degrees of plasticity, perhaps related to signal salience or top-down modulation of the auditory brainstem, or effects of neuromodulatory inputs ( Schofield and Hurley, 2018 ). Sottile et al (2017a , b ) demonstrated nicotinic receptors associated with GABAergic tectothalamic projections, and showed further that these receptors can change during aging. The authors commented on nicotinic receptor subunits expressed in the large GABAergic IC cells, but also showed evidence for such expression in smaller GABAergic cells.…”
Section: Discussionmentioning
confidence: 88%
“…Such suggestions are supported by electrophysiological data, associating communication problems with temporal processing deficits within the auditory brainstem (Caspary, Hughes, Schatteman, & Turner, 2006;Caspary, Schatteman, & Hughes, 2005), midbrain (Parthasarathy & Bartlett, 2011;Presacco, Simon, & Anderson, 2016a, 2016bWalton, Frisina, & O'Neill, 1998), or cortex (Mendelson & Ricketts, 2001; Presacco et al, 2016aPresacco et al, , 2016b. These age-related deficits in auditory processing throughout the central auditory pathways have been variously linked to alterations in: inhibitory signaling (Caspary, Ling, Turner, & Hughes, 2008), GABAergic transmission (Burianova, Ouda, Profant, & Syka, 2009;Cisneros-Franco, Ouellet, Kamal, & Villers-Sidani, 2018;Pal et al, 2019), cholinergic dysfunction (Sottile et al, 2017), parvalbumin positive (PV+) neurons (Cisneros-Franco et al, 2018;Gray, Engle, Rudolph, & Recanzone, 2014;Pal et al, 2019); and glial cells (Tremblay, Zettel, Ison, Allen, & Majewska, 2012). However, many studies investigating aging use old animals or animal-models of accelerated aging to investigate age-related changes within the auditory system, for example CBA/ CaJ mice beyond 80 weeks of age, C57/Bl6 mice (Sergeyenko, Lall, Liberman, & Kujawa, 2013) or Fisher Brown Norway rats (Cai, Montgomery, Graves, Caspary, & Cox, 2018).…”
Section: Introductionmentioning
confidence: 89%
“…These results support our stimulus choice aimed at simulating temporal processing deficits observed with ageing, which are partly mediated by neurotransmitter-deficits with ageing. Age-related changes in neurotransmission impact upon the function of descending and ascending projections to the MGB, which include decreased tonic GABA currents, as well as preand post-synaptic changes in cholinergic receptors, and are considered to be involved in gating/modulating MGB representations (Banay- Schwartz et al 1989;Richardson et al 2013b;Godfrey et al 2017;Sottile et al 2017a;Sottile et al 2017b). However, Richardson et al (2013a) failed to find evidence of age-related physiological changes in MGB function using short duration pure tone SSA paradigm (Richardson et al 2013a).…”
Section: Effects Of Ageing and Top-down Processes In The Medial Genicmentioning
confidence: 99%
“…They found a gain in MGB activity that lasted for 150 ms post-stimulation, which was associated with enhanced sound detection (Guo et al 2017). Few studies have investigated the effect of corticothalamic stimulation with ageing on MGB physiology (Sottile et al 2017a;Sottile et al 2017b). Apart from modulating MGB response properties, corticothalamic projections are implicated in the switching from temporal to rate code, possibly involving some combination of short-term NMDA/AMPA and long-term mGluR-dependent mechanisms (Lu et al 2001;Bartlett & Smith, 2002;Bartlett & Wang, 2007;Wang et al 2008;Rabang & Bartlett, 2011;Cai & Caspary, 2015).…”
Section: Effects Of Ageing and Top-down Processes In The Medial Genicmentioning
confidence: 99%
See 1 more Smart Citation